Constructing Superhydrophobicity by Self‐Assembly of SiO2@Polydopamine Core‐Shell Nanospheres with Robust Oil‐Water Separation Efficiency and Anti‐Corrosion Performance. (31st January 2023) - Shi, Zhen; Zeng, Hang; Yuan, Yusheng; Shi, Nan; Wen, Lin; Rong, Huawei; Zhu, Dapeng; Hu, Liang; Ji, Lianze; Zhao, Lizhong; Zhang, Xuefeng
Abstract: Vulnerable robustness of superhydrophobic materials have mightily hindered their practical applications. Herein, a controllable and effective strategy is demonstrated for constructing robust superhydrophobicity with aqueous hydrophobic interaction driving self‐assembly (HIDS), using polydopamine (PDA) as the binder and SiO2 particles as the nano‐sized structures to enable low‐adhesive property. The proposed strategy realizes the rapid interfacial assembly of PDA by manipulating the wetting properties of SiO2 @PDA core‐shell particles with hydrophobic modifier. The polyurethane (PU) sponges are facilely rendered superhydrophobic with remarkable robustness, stemming from the excellent adherence of HIDS enhanced covalent interaction between PDA and PU. Coated sponge possesses ultralong‐term stability during the oil‐water separation, the separation efficiency can be maintained at 98.8% even after 1000 cycle separations and strikingly, superhydrophobicity is still retained after 100 cycle abrasion with ultrahigh loading pressure of 49 kPa. Versatilely, the coatings can be assembled on various substrates through scalable dip coating for attaining superhydrophobicity, regardless of size, roughness, chemistry, and rigidity. The complete water‐repellent coatings on permanent magnet of Nd‐Fe‐B hold excellent anti‐corrosion properties without deteriorating the magnetic properties, exhibiting a low corrosion current density of 2.03 × 10 −8 A cm −2, which is three orders of magnitude lower than that of 1.30 × 10 −5 A cm −2 for bare Nd‐Fe‐B magnet. Abstract : A straightforward construction strategy toward robust superhydrophobic surfaces is reported, based on the hydrophobic interaction driving self‐assembly of polydopamine (PDA) coated SiO2 particles. Efficient solid‐liquid interfacial assembly is realized by manipulating the particle wetting properties. Covalent interaction between PDA and sponge endows strong adherence and excellent oil‐water separation performance with ultralong‐term stability.